Fifteen-minute consultation: How to undertake an effective video consultation for children, young people and their families. Issue 5 (28th September 2020) - Zhu, Hannah; John-Legere, Stacy; Butler, Mark; Hamilton, Emily; Turnbull, Jessica Ruth
Abstract : The COVID-19 pandemic has changed how we work in paediatrics with increasing use of virtual consultations. When optimised, a great deal can be achieved through video consultation compared with telephone, but accessibility and clinical risk need to be carefully considered and managed. This article aims to provide a structured approach with top tips for planning and delivering video consultations effectively in paediatrics.